Expression of ATP-sensitive potassium channels in human pregnant myometrium - Hui Ning; Hu Rong; Zhang Lanmei; Gao Lu; You Xingji; Xu Chen; Olson David M; Ni Xin (BMC, 2011)
Abstract Background Potassium channels play critical roles in the regulation of cell membrane potential, which is central to the excitability of myometrium. The ATP-sensitive potassium (KATP) channel is one of the most abundant potassium channels in myometrium. The objectives of this study were to investigate the protein expression of KATP channel in human myometrium and determine the levels of KATP channel in lower and upper segmental myometrium before and after onset of labour. Methods Both lower segmental (LS) and upper segmental (US) myometrial biopsies were collected at cesarean section from pregnant women not-in-labour (TNL) or in-labour (TL) at term. Protein expression level and cellular localization of four KATP channel subunits in US and LS myometrium were determined by Western blot analysis and immunohistochemistry, respectively. The contractile activity of myometrial strip was measured under isometric conditions. Results Four KATP channel subunits, namely Kir6.1, Kir6.2, SUR1 and SUR2B were identified in pregnant myometrium. While found in vascular myocytes, these subunits appear to be preferentially expressed in myometrial myocytes. Diazoxide, a KATP channel opener, inhibited the spontaneous contractility of pregnant myometrium, suggesting that the KATP channels are functional in human pregnant myometrium. Diazoxide was less potent in TL strips than that in TNL strips. Interestingly, expression of SUR1 was greater in TL than TNL tissues, although no differences were found for SUR2B in these two tissues. For both lower and upper segmental myometrium, Kir6.1 and Kir6.2 were less in TL compared with TNL tissues. Conclusions Functional KATP channels are expressed in human pregnant myometrium. Down-regulation of Kir6.1 and Kir6.2 expression in myometrium may contribute to the enhanced uterine contractility associated with the onset of labour.